Hubungan Kemandirian dengan Penyesuaian Diri pada Santri Pondok Pesantren Diniyyah Putri Lampung - Ulpa, Eska Prawisudawati; Zahara, Nur; Afifah, Sarah (ANFUSINA: Journal of Psychology, 2020)
AbstractSelf adjustment is an effort or an act for someone to interact properly with surroundings where he belong and can overcome obstacles or conflicts that comes from inner or outerside of him/herself so he/she can be accepted by neighborhood. This research intend to know the relation of independence with self adjustment on new students in Pondok Pesantren Diniyyah Putri Lampung. The Hypothesis submitted in this research is to know there is relation of independence with self adjustment on new Students in Pondok Pesantren Diniyyah Putri Lampung.Data collection method using two psychological scales which involve :scale self adjustment consists of 27 items which has coefficient realibility value amount α = 0,874, and independence scale consists of 47 items which has coefficient realibility value amount α = 0,884. These research subject are students in Pondok Pesantren Diniyyah Putri Lampung. Total Subject used are 100 students, subjects range aged 12 to 15 years old. Techniques used on this research is Proportional Random Sampling, with lottery way. Analysis technique used is Product moment pearson which helped with SPSS 22.0 for windows. Analyzed data results show that Rx.y = 0,352, and signification 0,000 where p < 0,01, which means there is significant relationship between independence with self adjustment on students, independence variable for self adjustment gives effective contribution amount 0,124, which shown by determination coefficient (R²) or amount 12,4 %. This thing shows that there is another 87,6 % affected  by other factors outside this research.